Spectrophotometric determination of Salicylamide one of the novel COVID -19 protocols via new design Flow Injection with Merging-Zone Technique - Al-Badri, Shurooq Badri; Muhamad, Yasmeen H. (Iraqi Journal of Science, 2024)
Recently, attention has turned to drugs like salicylamide for treating COVID-19. Several studies have reported simple, fast, and sensitive methods for measuring salicylamide levels. However, potential limitations remain regarding interference from other drugs and accuracy of results. To tackle this issue, researchers combined the standard addition technique with flow injection analysis. As part of this investigation, the reaction involving Fe (III), salicylamide, and 1,10-phenanthroline at a temperature of 55°C was examined using a spectrophotometer set at a wavelength of 528 nm. Thus, the new design was able to show an excellent linearity over the concentration range of (2-30 μg/mL) and (25-300 μg/mL), with correlation coefficients ( ) of 0.9669 and 0.9781, respectively. In addition, physical and chemical variables were optimized to obtain the best results. There was a significant positive correlation between the new design and  NIR micro-spectrometers device (handheld) outcomes.